A comprehensive analysis of polymorphic variants in steroid hormone and insulin‐like growth factor‐1 metabolism and risk of in situ breast cancer: Results from the Breast and Prostate Cancer Cohort Consortium. Issue 6 (17th November 2017) - Barrdahl, Myrto; Canzian, Federico; Gaudet, Mia M.; Gapstur, Susan M.; Trichopoulou, Antonia; Tsilidis, Kostas; van Gils, Carla H.; Borgquist, Signe; Weiderpass, Elisabete; Khaw, Kay‐Tee; Giles, Graham G.; Milne, Roger L.; et al.
Abstract : We assessed the association between 1, 414 single nucleotide polymorphisms (SNPs) in genes involved in synthesis and metabolism of steroid hormones and insulin‐like growth factor 1, and risk of breast cancer in situ (BCIS), with the aim of determining whether any of these were disease specific. This was carried out using 1, 062 BCIS cases and 10, 126 controls as well as 6, 113 invasive breast cancer cases from the Breast and Prostate Cancer Cohort Consortium (BPC3). Three SNPs showed at least one nominally significant association in homozygous minor versus homozygous major models. ACVR2A ‐rs2382112 (ORhom  = 3.05, 95%CI = 1.72–5.44, Phom  = 1.47 × 10 −4 ), MAST2 ‐rs12124649 (ORhom  = 1.73, 95% CI =1.18–2.54, Phom  = 5.24 × 10 −3 ), and INSR ‐rs10500204 (ORhom  = 1.96, 95% CI = 1.44–2.67, Phom =1.68 × 10 −5 ) were associated with increased risk of BCIS; however, only the latter association was significant after correcting for multiple testing. Furthermore, INSR ‐rs10500204 was more strongly associated with the risk of BCIS than invasive disease in case‐only analyses using the homozygous minor versus homozygous major model (ORhom  = 1.78, 95% CI = 1.30–2.44, Phom  = 3.23 × 10 −4 ). The SNP INSR ‐rs10500204 is located in an intron of the INSR gene and is likely to affect binding of the promyelocytic leukemia (PML) protein. The PML gene is known as a tumor suppressor and growth regulator in cancer. However, it is not clear on what pathway the A‐allele of rs10500204 could operate to influence the binding of the protein. Hence, functional studies are warranted to investigate this further. Abstract : What's new? While a growing number of common, low‐penetrance susceptibility loci for invasive breast cancer are being identified, comparatively few attempts to detect single nucleotide polymorphisms (SNPs) specific for breast carcinoma in situ (BCIS) have been made. However, it is important to identify disease‐specific genetic risk factors, since only a fraction of BCIS tumors will progress to the invasive stage. Our study indicates a possible association between the A‐allele of INSR ‐rs10500204 and BCIS risk. INSR ‐rs10500204 is likely to affect binding of the promyelocytic leukemia protein, a tumor suppressor and growth regulator in cancer. Further epidemiological and functional studies are warranted to confirm the finding.